Differences of temporomandibular joint condyle morphology with and without clicking using digital panoramic radiograph - Pramanik, Farina; Firman, Ria Noerianingsih; Sam, Belly (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Introduction: Clicking is the most common clinical symptom in patients with Temporomandibular Disorder (TMD). Lacking attention by either the patient or dentist, many patients were found to have suffered from morphologic alteration of the condyles seen in the panoramic radiograph inadvertently. The purpose of the study was to determine the differences of condyle morphology of the Temporomandibular Joint (TMJ) with and without the existence of clicking by means of digital panoramic radiographs. Methods: This study was based on an analytic descriptive research, whereas subjects are digital panoramic radiographs taken from clicking and non-clicking patients at the Radiology Installation of Dental Hospital Universitas Padjadjaran. 16 samples of each group were chosen in a non-random purposive sampling manner. Results: The research showed the mean of condyle morphology, HOC heightÂ on clicking (6.31 mm) was shorter than the non clicking (7.63 mm), the width of HOC on clicking (10.38 mm) was higher than the non clicking (10.22 mm) and height of the processus condylaris on clicking (19.70 mm) was shorter than non clicking (20.04 mm). Ratio of the high of HOC, width of HOC and high of processus condylaris were 12.13 (clicking), and 12.63 (non-clicking). Conclusion: There was no significant difference between the morphology of the TMJ condyle between clicking and not clicking group, except on high of HOC.